Dying for an iPhone: The Labour Struggle of China’s New Working Class - Jenny Chan (tripleC: Communication, Capitalism & Critique)
The presented sociological research analyses the ways in which the integration of the electronics manufacturing industry in global supply chains has intensified labour conflicts and class antagonism. The Taiwanese transnational corporation Foxconn Technology Group holds more than 50 percent of market share in global electronics manufacturing. Its 1.4 million employees in China far exceed its combined workforce in 28 other countries that comprise its global empire.